Genetic mapping of QTL for Fusarium head blight resistance in winter wheat cultivars Art and Everest - Clinesmith, Marshall (Kansas State University, 2016)
Fusarium head blight (FHB) is a fungal disease, mostly commonly associated with F. graminearum, which affects cereal crops such as wheat resulting in substantial yield losses and reductions in grain quality. The onset of the disease can occur rapidly when warm, wet or humid weather coincides with flowering in the spring. The pathogen also produces mycotoxins such as deoxynivalenol (DON) that accumulate in the grain and can be toxic to humans and animals. This results in additional economic losses as contaminated grain must be discarded or blended to reduce the amount of toxin in order to meet federal regulatory limits. Development and deployment of resistant cultivars has proved to be an effective method to combat the disease, and many resistant sources have been reported in the literature with the majority of major resistance coming from Chinese landraces. Transferring resistance from these sources into cultivars adapted to the U.S. has been a slow process due to linkage of FHB resistance genes with poor agronomic traits. Therefore, it is important for breeders to search for sources of resistance in native material adapted to their local conditions. In this study, we aimed to identify quantitative trait loci (QTL) for resistance to spread of FHB within the head (Type II resistance), accumulation of DON toxin in grain (Type III resistance), and resistance to kernel infection (Type IV resistance). Plant material consisted of 148 doubled haploid (DH) lines from a cross between the two moderately resistant hard red winter wheat (HRWW) cultivars Art and Everest. The study was conducted for two years using a point inoculation technique in a greenhouse in Manhattan, KS. Three QTL conferring resistance to FHB traits were detected on chromosomes 2D, 4B, and 4D. The QTL on chromosomes 4B and 4D overlapped with the major height genes Rht1 and Rht2, respectively. Plant height has shown previous associations with FHB, though the underlying cause of these associations is not well understood. The majority of results have reported increased susceptibility associated with shorter plant types; however, in this study, the haplotype analysis for the Rht-B1 and Rht-D1 loci showed an association between the dwarfing alleles and increased resistance to FHB. This suggests either pleiotropic effects of these loci or perhaps linkage with nearby genes for FHB resistance. Markers close to the peaks of the FHB resistance QTL have the potential for Kompetitive Allele Specific PCR (KASP) marker development and subsequent use in marker assisted selection (MAS) to help improve overall FHB resistance within breeding programs.
Keywords: Fusarium head blight; Quantitative trait loci; Hard red winter wheat